2006
DOI: 10.1007/s00018-005-5467-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that miRNAs are different from other RNAs

Abstract: An examination of 513 known pre-miRNAs and 237 other RNAs (tRNA, rRNA, and mRNA) revealed that miRNAs were significantly different from other RNAs (p < 0.001). miRNA genes were less conserved than other RNA genes, although their mature miRNA sequences were highly conserved. The A+U content of pre-miRNAs was higher than non-coding RNA (p < 0.001), but lower than mRNAs. The nucleotides in pre-miRNAs formed more hydrogen bonds and base pairs than in other RNAs. miRNAs had higher negative adjusted minimal folding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
443
8
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 511 publications
(502 citation statements)
references
References 42 publications
49
443
8
2
Order By: Relevance
“…However, a majority of the pre-miRNAs are 40 to 82 nt (26 out of 51, or 51%) in length (Table 1), then 83 to 125 = 12 (23%), 126 to 168 = 10 (20%), 169 to 211 = 1 (2%), and 212 to 254 = 2 (4%). Mature miRNA arm locations, length distribution of miRNAs, and their precursor sequences are similar to previous reports in other plant species (Zhang et al, 2006b(Zhang et al, , 2007bDin et al, 2014). MFE is very important for RNAs forming their secondary structures.…”
Section: Characterization Of Micrornas In the Genus Coffeasupporting
confidence: 86%
“…However, a majority of the pre-miRNAs are 40 to 82 nt (26 out of 51, or 51%) in length (Table 1), then 83 to 125 = 12 (23%), 126 to 168 = 10 (20%), 169 to 211 = 1 (2%), and 212 to 254 = 2 (4%). Mature miRNA arm locations, length distribution of miRNAs, and their precursor sequences are similar to previous reports in other plant species (Zhang et al, 2006b(Zhang et al, , 2007bDin et al, 2014). MFE is very important for RNAs forming their secondary structures.…”
Section: Characterization Of Micrornas In the Genus Coffeasupporting
confidence: 86%
“…Generally speaking, the lower the MFE value, the more stable the secondary structure of a RNA sequence (Zhang et al, 2006). In the present study, our results showed that the value of MFEs range from -18.1 kcal/mol to −74.7 kcal/mol with average value of −27.02 ± 8.19 kcal/mol (Fig.…”
Section: Characterization Of Mirnas In Rainbow Troutsupporting
confidence: 60%
“…As well, some parameters describing the folded structure are common to other SVM approaches including minimum folding energy index (MFEI), adjusted minimum folding energy (AMFE) (Zhang et al 2006), normalized pairing propensity (Ng Kwang Loong and Mishra 2007), and loop length. The parameters that are unique to this type of sequencing data are descriptors of the seed itself and its positioning within the pre-miRNA structure.…”
Section: Novel Microrna Predictionmentioning
confidence: 99%